2017
DOI: 10.1371/journal.pone.0170394
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Modified Child-Turcotte-Pugh Classification System Utilizing Insulin-Like Growth Factor-1 for Patients with Hepatocellular Carcinoma in an HBV Endemic Area

Abstract: BackgroundRecently, a modified insulin-like growth factor-1 (IGF)–Child-Turcotte-Pugh (CTP) classification was proposed to improve the original CTP classification. This study aimed to validate the new IGF-CTP classification system as a prognostic maker for patients with hepatocellular carcinoma (HCC) in a hepatitis B virus endemic area.MethodsWe conducted a post-hoc analysis of a prospective cohort study. We used Harrell’s C-index and U-statistics to compare the prognostic performance of both IGF-CTP and CTP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It was shown that serum IGF1 levels predict prognosis in cases of HCC. Lower plasma IGF1 levels were significantly correlated with advanced clinical parameters, shorter time to progression and poor overall survival [ 140 , 141 , 145 , 146 , 147 , 148 , 149 ], even in patients that underwent transarterial chemoembolization (TACE) [ 148 , 149 , 150 , 151 , 152 ] or other types of curative treatment, such as surgical resection or percutaneous ethanol injection [ 150 ]. Longitudinal observation of HCC cases (median follow-up period of 41.8 months) proved that IGF1 level was an independent predictor of poorer survival [ 151 ].…”
Section: Evidence From Epidemiologic and Clinicopathological Studimentioning
confidence: 99%
“…It was shown that serum IGF1 levels predict prognosis in cases of HCC. Lower plasma IGF1 levels were significantly correlated with advanced clinical parameters, shorter time to progression and poor overall survival [ 140 , 141 , 145 , 146 , 147 , 148 , 149 ], even in patients that underwent transarterial chemoembolization (TACE) [ 148 , 149 , 150 , 151 , 152 ] or other types of curative treatment, such as surgical resection or percutaneous ethanol injection [ 150 ]. Longitudinal observation of HCC cases (median follow-up period of 41.8 months) proved that IGF1 level was an independent predictor of poorer survival [ 151 ].…”
Section: Evidence From Epidemiologic and Clinicopathological Studimentioning
confidence: 99%
“…The second study was done with 393 Korean patients with HCC, and the vast majority (78.9%) of patients in the study were hepatitis B virus-positive. 34 Although there was a trend towards a better prediction of survival by the IGF-CTP classification system compared to the original CTP system, the difference (14%) between the two classification systems was not statistically significant. However, the Korean study included 71.5% of early-intermediate stage HCC patients, defined as BCLC stages 0-B, who are classic candidates for surgery, transplant, ablation, and local therapy procedures, which may have affected their survival independently, Table 6 .…”
Section: Discussionmentioning
confidence: 80%
“…The IGF-CTP classification was developed and validated in two US cohorts where most patients had viral hepatitis as the underlying liver disease for HCC [ 14 , 17 ]. In the Egyptian validation study, all patients had viral-induced HCC [ 26 ], as was also the case in the Korean cohort, especially HBV (78.9%) [ 27 ] (Table 5 ). In contrast, our cohort had alcohol-induced liver disease as the most frequent underlying cause of HCC in 44.4% and viral hepatitis in only 24.6% of cases.…”
Section: Discussionmentioning
confidence: 84%
“…In a cohort with 393 Korean patients with HCC, mostly with underlying chronic viral hepatitis B, the IGF-CTP classification system showed no statistically significant improvement of stratification but demonstrated a trend towards better prediction of survival. In that analysis, only 14% of patients showed a difference between IGF-CTP class and CTP class [ 27 ]. In our cohort, 35.6% of patients were reclassified when using IGF-CTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation